2015
DOI: 10.1063/1.4932522
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional machining of carbon nanotube forests using water-assisted scanning electron microscope processing

Abstract: We demonstrate that vertically aligned carbon nanotubes (CNTs) can be precisely machined in a low pressure water vapor ambient using the electron beam of an environmental scanning electron microscope. The electron beam locally damages the irradiated regions of the CNT forest and also dissociates the water vapor molecules into reactive species including hydroxyl radicals. These species then locally oxidize the damaged region of the CNTs. The technique offers material removal capabilities ranging from selected C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Because the SEM-based techniques rely on a multiple-step chemical process, numerous processing variables may influence the milling rate and precision of the process. It has been previously observed that increasing acceleration voltage and beam current directly increase the milling rate because of an increased energy flux, as expected 11 . The effect of chamber pressure is less obvious.…”
Section: Introductionsupporting
confidence: 73%
“…Because the SEM-based techniques rely on a multiple-step chemical process, numerous processing variables may influence the milling rate and precision of the process. It has been previously observed that increasing acceleration voltage and beam current directly increase the milling rate because of an increased energy flux, as expected 11 . The effect of chamber pressure is less obvious.…”
Section: Introductionsupporting
confidence: 73%
“…These species then etch neighboring carbon atoms of the SWNTs to form CO, CO 2 , and various hydrocarbons. A similar etching phenomenon was reported in studies on CNT cutting 6 and the machining of CNT forests, 38 where CNTs were cut with a low-energy focused electron beam (with SEM) in the presence of water vapor inside the chamber.…”
Section: Threshold Field For Gap Extension: Voltage Vs Gap Sizesupporting
confidence: 68%
“…To do so, the CNT growth catalyst could be deposited directly onto the roll before CNT growth, or CNTs could be grown on large-area flat substrates (for example, glass plates) and then transferred to a flexible substrate ( 75 ). In addition, to avoid the use of photolithography for stamp fabrication, CNT forests can be grown from a nonpatterned catalyst layer and then structured using subtractive methods ( 76 , 77 ) such as laser ablation.…”
Section: Discussionmentioning
confidence: 99%